Sleeve Gastrectomy and Pancreatic Omentoplasty improve B-cell status in Rats by increasing VEGF, PDX1, islet of Langerhans area, and B-cell count - Mughni, Abdul; Reno Rudiman; Pemayun , Tjokorda Gde Dalem; Bella Renata; Endang Mahati; Suharyo Hadisaputro; Riwanto, Ignatius (Journal of Liaquat University of Medical & Health Sciences, 2025)
OBJECTIVE: To analyze the effect of sleeve gastrectomy and pancreatic omentoplasty on pancreatic B-cell status by evaluating the levels of PDX1 and VEGF. METHODOLOGY: This experimental animal research was done with a post-test-only control design. This research was conducted at the Laboratory of Integrated Research and Development, Universitas Gadjah Mada, Yogyakarta, Indonesia, from April to June 2022. The subjects consist of obese and T2DM rats, divided into sleeve gastrectomy (K1), sleeve gastrectomy with pancreatic omentoplasty (K2), positive control (K3), and normal rats in negative control (K4). On the 10th day post-surgery, VEGF and PDX1 were measured using polymerase chain reaction, with histologic examination of the Langerhans islet area and pancreatic ?-cell count. RESULTS: Significant differences in Langerhans islet area and pancreatic ?-cell count were found between K1 and K2, and K2 and K3 (p < 0.01). PDX1 expression was highest in K4, followed by K2, K1, and K3, with significant differences between K4 and K3, K2 and K3, and K1 and K3 (p < 0.01). VEGF expression in K2 was significantly higher than in K1 (p = 0.006), K3 (p = 0.004), and K4 (p = 0.001). CONCLUSION: Sleeve gastrectomy and pancreatic omentoplasty improve pancreatic B-cells status by increasing VEGF, PDX1, Langerhans islet area, and pancreatic ?-cell count compared to sleeve gastrectomy alone.